Case series of three different scenarios with drug-induced Brugada patterns: fact or fiction? - Serkan Asil; Uğur Canpolat; Ergün Barış Kaya; Kudret Aytemir; Giray Kabakçı (KARE Publishing, 2017)
Brugada syndrome is an inherited cardiac arrhythmia condition characterized by coved-type ST elevation and J point elevation of at least 2 mm in at least 2 of the right precordial electrocardiogram (ECG) leads (V1-3). An increasing number of noncardiac agents, including psychotropic and anesthetic drugs, have been shown to induce a characteristic Brugada ECG pattern, predisposing the patient to fatal ventricular arrhythmias. However, there are scarce data regarding the clinical significance. In this case series, a typical Brugada pattern was unmasked by lithium, valproic acid, and thiocolchicoside; however, the clinical scenario was different in all 3 cases, ranging from an asymptomatic patient to sudden cardiac arrest.